Web-based decision-aid to assist help-seeking choices for young people who self-harm: outcomes from a randomised controlled feasibility trial - Rowe, Sarah L.; Patel, Krisna; French, Rebecca S.; Henderson, Claire; Ougrin, Dennis; Slade, Mike; Moran, Paul (JMIR Publications, 2018)
Background: Adolescents who self-harm are often unsure how or where to get help. We developed a web-based personalised decision aid (DA), designed to support young people in decision-making about seeking help for their self-harm. Objective: Our aim was to evaluate the feasibility and acceptability of the DA intervention and the randomised controlled trial (RCT) in a school setting. Methods: We conducted a 2-group, single blind, randomised controlled feasibility trial in a school setting. Participants aged 12-18 years who reported self-harm in the past 12 months were randomised to either a web-based DA or to general information about mood and feelings. Feasibility of recruitment, randomisation and follow-up rates were assessed, as was acceptability of the intervention and study procedures. Descriptive data were collected on outcome measures examining decision-making and help-seeking behaviour. Qualitative interviews were conducted with young people, parents/carers and staff, and subjected to thematic analysis to explore their views of the DA and study processes. Results: Parental consent was a significant barrier to young people participating in the trial, with only 208 (18%) of the 1,164 parent/guardians contacted for consent responding to study invitations. Where parental consent was obtained, we were able to recruit 82% (n=170) of young people into the study. Of those young people screened, 14% (n=23) had self-harmed in the past year. Ten participants were randomised to receiving the DA and 13 were randomised to the control group. Four-week follow-up assessments were completed with all participants. The DA had good acceptability but qualitative interviews suggested that a DA that addressed broader mental health problems such as depression, anxiety and self-harm may be more beneficial. Conclusions: A broad-based mental health DA addressing a wide range of psychosocial problems may be useful for young people. The requirement for parental consent is a key barrier to intervention research on self-harm in the school setting. Adaptations to the research design and/or the intervention are needed before generalisable research about DAs can be successfully conducted in a school setting.